2022
DOI: 10.29309/tpmj/2022.29.07.6861
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy in diabetic patients versus diabetic with co-morbid hypertensive patients.

Abstract: Objectives: To find out severity of diabetic retinopathy in diabetic versus diabetic with co-morbid hypertensive patients in type II diabetes mellitus. Study Design: Comparative study. Setting: KDA Teaching Hospital Kohat. Period: March 2017 to December 2020. Material & Methods: This comparative study focused on severity of diabetic retinopathy was conducted on only type II diabetic patients versus type II diabetic with co-morbid hypertensive patients. Two groups A for diabetic and B for diabetic with co-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They concluded that gray-scale ultrasonography was the initial imaging modality used in most patient cases, due to the fact that it was readily available, simple, cost-effective, nonionizing, noninvasive, and reliable modality for ocular diagnostics among DM and hypertensive patients. 20 Furthermore, they suggested that sonography must be used routinely for ocular evaluation of DM and hypertensive patients. 20 However, in this study it would be worthwhile to use spectral Doppler, within the OA, to routinely predict changes in color Doppler parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that gray-scale ultrasonography was the initial imaging modality used in most patient cases, due to the fact that it was readily available, simple, cost-effective, nonionizing, noninvasive, and reliable modality for ocular diagnostics among DM and hypertensive patients. 20 Furthermore, they suggested that sonography must be used routinely for ocular evaluation of DM and hypertensive patients. 20 However, in this study it would be worthwhile to use spectral Doppler, within the OA, to routinely predict changes in color Doppler parameters.…”
Section: Discussionmentioning
confidence: 99%
“…20 Furthermore, they suggested that sonography must be used routinely for ocular evaluation of DM and hypertensive patients. 20 However, in this study it would be worthwhile to use spectral Doppler, within the OA, to routinely predict changes in color Doppler parameters. Another research study completed by Dimitrova and Kato has suggested that spectral Doppler is a widely used diagnostic method for evaluating ocular circulation and should be used to assess blood velocity parameters in the OA, CRA, and PCA.…”
Section: Discussionmentioning
confidence: 99%